Noncontiguous finished genome sequence and description of Planococcus massiliensis sp. nov., a moderately halophilic bacterium isolated from the human gut. (March 2016) - Seck, E.H.; Sankar, S.A.; Khelaifia, S.; Croce, O.; Robert, C.; Couderc, C.; Di Pinto, F.; Sokhna, C.; Fournier, P.-E.; Raoult, D.; Lagier, J.-C.
Abstract: We propose the main phenotypic characteristics and the complete genome sequence and annotation of Planococcus massiliensis strain ES2 T (= CSUR P1103 = DSM 28915), the type strain of P. massiliensis sp. nov., isolated from a faeces sample collected from a healthy Senegalese man. It is an aerobic, Gram-positive, moderately halophilic, motile and rod-shaped bacterium. The 3 357 017 bp long genome exhibits a G+C content of 46.0% and contains 3357 protein-coding genes and 48 RNA genes.